2016
DOI: 10.1149/2.0621610jes
|View full text |Cite
|
Sign up to set email alerts
|

The Formation Mechanism and Electrochemical Cyclic Stability of the Single-Phase PrnMgNi5n-1(n= 2, 3, 4) Hydrogen Storage Alloy

Abstract: In this work, we prepared the single-phase Pr 2 MgNi 9 , Pr 3 MgNi 14 and Pr 4 MgNi 19 alloys via strictly controlling the zoning sintering and annealing process with PrMgNi 4 and PrNi 5 precursors, and systematically studied the formation mechanism and capacity degradation causes of the alloys. It is found that the successive peritectic reactions, of which the initial alloy phases are the molten PrMgNi 4 phase and the solid phase PrNi 5 , occurred among the AB 3 , A 2 B 7 and A 5 B 19 -type phases, and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…All the electrochemical measurement specific items system could refer to our previous reports. 24 For electrochemical P-C test, the fully charged electrodes were discharged at a current density of 60 mA g -1 for 0.5 h, followed by an interval of 0.5 h until reaching a cutoff potential of -0.6 V (vs. Hg/HgO reference electrode). The equilibrium potential (E eq ) was collected from the voltages after every interval.…”
Section: Methodsmentioning
confidence: 99%
“…All the electrochemical measurement specific items system could refer to our previous reports. 24 For electrochemical P-C test, the fully charged electrodes were discharged at a current density of 60 mA g -1 for 0.5 h, followed by an interval of 0.5 h until reaching a cutoff potential of -0.6 V (vs. Hg/HgO reference electrode). The equilibrium potential (E eq ) was collected from the voltages after every interval.…”
Section: Methodsmentioning
confidence: 99%
“…According to the certain combinations of the two subunits, the RE-Mg-Ni-based alloys can be divided into the AB 3 -, A 2 B 7 -, A 5 B 19 -, and AB 4 -type superlattice phases, and each phase has an allotrope with either a hexagonal 2H (CeNi 3 -, Ce 2 Ni 7 -, or Pr 5 Co 19 -type) structure or a rhombohedral 3R (PuNi 3 -, Gd 2 Co 7 -, or Ce 5 Co 19 -type) structure. [7][8][9][10] Among all the structure above, the RE-Mg-Ni-based alloy with A 2 B 7 -type structure has been widely studied because of its superior overall electrochemical properties. [11][12][13] Zhang et al 14 reported that the A 2 B 7 -type La 1.5 Mg 0.5 Ni 7 alloy showed superior electrochemical properties, with a maximum discharge capacity of 400 mAh g -1 and 84.2% discharge capacity retention after 100 charge/discharge cycles.…”
mentioning
confidence: 99%
“…In our group, partical of the electrochemical properites of the single-phase Pr n MgNi 5n-1 (n = 2, 3, 4) hydrogen storage alloy has been studied and reported. 10 As we all know that the Laves subunits and the atomic numbers for 2H-and 3R-type structure are different, [16][17][18] and the difference leads to the different electrochemical properites between 2H and 3R phases. Wu et al 19 obtained the La 0.59 Nd 0.14 Mg 0.27 Ni 3.3 alloy composed of 2Hand 3R-type phases via annealing, and reported the electrochemical and kinetic properties of the alloy electrodes, which the cycling stability at the 100 th cycle increased from 88.5% to 92.4%, and the HRD at 5C increased from 58.8% to 66.3%, as the 2H-A 2 B 7 phase increased from 28 wt% to 97 wt%.…”
mentioning
confidence: 99%